Industrial training report at RICAEN / Nelly Masdiana Abdullah - Abdullah, Nelly Masdiana (Universiti teknologi MARA, Perlis, 2023)
This report outlines my experience during the industrial training at RICAEN, the Research, Industry, Community, Alumni, Entrepreneurship, and Network unit at Universiti Teknologi MARA, Perlis Branch. The internship spanned 6 months, encompassing 24 weeks, starting from March 1st, 2023, and concluding on August 15th, 2023. During this period, I was assigned to the MASMED unit, representing the Malaysian Academy of SME & Entrepreneurship Development, with Miss Siti Sarina Sulaiman as my supervisor, who serves as the MASMED coordinator. Assisting me in my tasks was Madam Nur Jazillah Mohamad, also a member of the MASMED team. RICAEN plays a crucial role at UiTM, managing industrial collaborations between UiTM Perlis and other local or international universities. Moreover, it actively engages with the community, students, and alumni, conducts research and publications, and fosters a spirit of entrepreneurship among students. This experience provided me with invaluable skills, knowledge, and insights that will undoubtedly prove beneficial in my future endeavors.